Predicting Obsessive-compulsive behavior and Phobic Anxiety among Students of Medical Sciences: The role of the Concept of God - Ali Akbar Haddadi kuhsar; Bagher Ghobari Bonab (Shahid Beheshti University of Medical Sciences, 2018)
For downloading the full-text of this article please click here. Background and Objective:Theconcept of God which is conveyed to individuals by means of oral and cultural media is a conceptual understanding of people about attributes of God and is closely associated with psychological health of individuals. Having said that, the aim of the current research was predicting obsessive-compulsive behavior and phobic anxiety in students of Medical Sciences in 2014, examining the role of the concept of God in this regard. Method: In this descriptive-correlational study, whose statistical population was the students at Tehran University of Medical Sciences, 367 students were selected by proportional stratified sampling. God Concept Scaleand Scales of Obsessive-Compulsive and Phobic Anxiety of Symptoms Checklist-90R were administered on them. All ethical issues were observed in this study and the researchers declared no conflict of interests. Results: Multiple regression analysis of the data indicated that obsessive-compulsive behavior and phobic anxiety of university students can be predicted by the way they frame the concept of God. Moreover, the findings revealed that the male students who had a positive concept of God were lower in phobic anxiety (r=24; p<0.05). However, the female univesity students who had a positive concept of God were lower in obsessive-compulsive behavior (r=28; p<0.05). Conclusion: According to the findings, it can be concluded that obsessive-compulsive behavior and phobic anxiety of university students are subject to their concept of God. For downloading the full-text of this article please click here.